(PVA/Chitosan/Fucoidan)-Ampicillin: A Bioartificial Polymeric Material with Combined Properties in Cell Regeneration and Potential Antibacterial Features - Bernal-Ballen, Andres; Lopez-Garcia, Jorge-Andres; Ozaltin, Kadir (Polymers, 2019)
Chitosan, fucoidan, and polyvinyl alcohol are categorized as polymers with biomedical applications. Ampicillin, on the other hand, is considered as an important antibiotic that has shown effectivity in both gram-positive and gram-negative micro-organisms. The aforementioned polymers possess unique properties that are considered desirable for cell regeneration although they exhibit drawbacks that can affect their final application. Therefore, films of these biomaterials were prepared and they were characterized using FTIR, SEM, XRD, degree of swelling and solubility, and MTT assay. The statistical significance of the experiments was determined using a two-way analysis of variance (ANOVA) with p < 0.05. The characterization techniques demonstrated that the obtained material exhibits properties suitable for cell regeneration, and that a higher concentration of natural polymers promotes cells proliferation to a greater extent. The presence of PVA, on the other hand, is responsible for matrix stability and dictates the degree of swelling and solubility. The SEM images demonstrated that neither aggregations nor clusters were formed, which is favorable for the biological properties without detrimental to the morphological and physical features. Cell viability was comparatively similar in samples with and without antibiotic, and the physical and biological properties were not negatively affected. Indeed, the inherent bactericidal effect of chitosan was reinforced by the presence of ampicillin. The new material is an outstanding candidate for cell regeneration as a consequence of the synergic effect that each component provides to the blend.
Keywords: bioartificial polymeric material; cell proliferation; chitosan; polyvinyl alcohol; fucoidan; ampicillin